(untitled) (Ameghiniana, 2017)
The octodontoid rodent Acarechimys was abundant during the early Miocene and had the widest temporal and geographic distribution of any extinct caviomorph. Despite this extensive fossil record Acarechimys has not been well characterized. In this work, we systematically revise Acarechimys, describe new early–middle Miocene fossils from Argentina and Bolivia, corroborate its monophyly, and study its evolutionary history. Acarechimys has brachydont molars, retained deciduous premolars, four crests on upper molars, lowers with variably developed mesolophid and metalophulid II, and absence of mental foramen in the mandible. Acarechimys includes: Acarechimys leucotheae (late Oligocene, Chubut, Argentina), A. gracilis and A. constans (early Miocene, Chubut and Santa Cruz, Argentina), and A. minutus and A. minutissimus (early– middle Miocene of Patagonia Argentina, Bolivia, and Colombia). The temporal and geographic distributions suggest that Acarechimys could have evolved in Patagonia, by the early late Oligocene. Its acme was during the late early Miocene in Southern Patagonia. By the middle Miocene, Acarechimys decreased in diversity and was last recorded in high latitudes of South America (Patagonia). In lower latitudes, the oldest record is from the late early Miocene of Chucal, northern Chile, and during the late middle Miocene, the genus is recorded in localities of Colombia, Bolivia, and Peru. The available evidence suggests that Acarechimys was probably not present in lower latitudes (N of 30° S) before the early Miocene. The reasons Acarechimys dispersed northward at this time remain to be elucidated, but the timing coincides with a massive disappearance of other octodontoids from Patagonia. Resumen. REVISIÓN SISTEMÁTICA E HISTORIA EVOLUTIVA DE ACARECHIMYS PATTERSON EN KRAGLIEVICH, 1965 (RODENTIA, CAVIOMORPHA, OCTODONTOIDEA). El roedor octodontoideo Acarechimys fue abundante durante el Mioceno temprano y tuvo la distribución geográfica y temporal más amplia para un caviomorfo viviente. A pesar de su amplio registro fósil Acarechimys nunca fue caracterizado correctamente. En este trabajo, realizamos la revisión sistemática de Acarechimys, describimos nuevos materiales del Mioceno temprano–medio de Argentina y Bolivia, corroboramos su monofilia y estudiamos su historia evolutiva. Acarechimys presenta dientes braquiodontes, retención de premolares deciduos, cuatro crestas en molares superiores, desarrollo variable del mesolófido y el metalofúlido II en molares inferiores y ausencia de foramen mentoniano en la mandíbula. Acarechimys incluye: Acarechimys leucotheae (Oligoceno tardío, Chubut, Argentina), A. gracilis y A. constans (Mioceno temprano, Chubut y Santa Cruz, Argentina), y A. minutus y A. minutissimus (Mioceno temprano–medio de Patagonia Argentina, Bolivia y Colombia). Su distribución temporal y geográfica sugiere que Acarechimys habría evolucionado en Patagonia en el Oligoceno tardío-temprano. Su acmé fue en el Mioceno temprano-tardío en el sur de Patagonia. Para el Mioceno medio Acarechimys disminuyó su diversidad y tiene su último registro en latitudes altas de América del Sur (Patagonia). En latitudes bajas, el registro más antiguo proviene del Mioceno temprano tardío de Chucal, norte de Chile, y durante el Mioceno medio se lo registra en localidades de Colombia, Bolivia y Perú. La evidencia disponible sugiere que Acarechimys probablemente no estuvo presente en bajas latitudes (N de 30ºS) antes del Mioceno temprano. Las causas de su dispersión hacia el norte deben ser todavía estudiadas, aunque la misma coincide con la desaparición masiva de octodontoideos en Patagonia.